Circulating levels of soluble EMMPRIN (CD147) correlate with levels of soluble glycoprotein VI in human plasma. (December 2014) - Pennings, G. J.; Yong, A. S. C.; Wong, C.; Al-Tamimi, M.; Gardiner, E. E.; Andrews, R. K.; Kritharides, L.
Abstract Extracellular matrix metalloproteinase inducer (EMMPRIN; CD147), which binds to the platelet-specific collagen receptor glycoprotein (GP) VI, is expressed in a range of cell types including platelets and leukocytes, and has been implicated in neoplastic disease and atherosclerotic coronary disease. Both CD147 and GPVI can be shed from cell membranes and detected in plasma. However, while the relationship between soluble CD147 (sCD147), soluble GPVI (sGPVI) and standard markers of platelet activation has received little attention, such analysis may help reveal pathways mediating release of sCD147. We investigated the relationship between sCD147 and platelet markers including sGPVI, soluble and platelet-bound CD62P (P-selectin), active αIIbβ3 (assessed by PAC-1 binding) and platelet CD147 in 25 patients with stable angina pectoris (SAP), 13 patients with no coronary artery disease (CAD) and 10 healthy donors. Plasma levels of sCD147 significantly correlated with sGPVI (r = 0.46, p = .004), but did not correlate with any other platelet markers examined. Linear regression analysis identified that sCD147 levels could be predicted by sGPVI levels (β = .445, p = 0.003) and age (β = 0.304, p = 0.038), but were independent of potential clinical confounders such as CAD, diabetes and medication usage. As sCD147 strongly correlates with platelet-specific sGPVI, a common platelet source and/or mechanism of release may contribute to sCD147 levels in vivo.